Floquet modes‐based asymptotic analysis of scattering from FSS‐type reflectarray/transmitarray for near‐zone‐focused radiations. Issue 12 (29th December 2015) - Chou, Hsi‐Tseng; Tuan, Shih‐Chung
Abstract: This paper presents the asymptotic formulation of ray fields in the decomposition of electromagnetic (EM) scattering mechanisms from a one‐dimensional, semi‐infinite, and periodic array when it is illuminated by a line source. This technique can be applied to analyze the passive FSS (frequency selective surface)‐type periodic structures with identical elements, or the reflectarray‐ and transmitarray‐type antennas that are phased to radiate EM fields focused in the near zone of the array aperture. The solutions are built up based on the Floquet mode expansion of the scattering fields and are obtained by asymptotically evaluating the resulted integrals to express the fields in terms of reflected/transmitted and edge diffracted fields as previously addressed in the framework of uniform geometrical theory of diffraction. The theoretical investigations over the scattering mechanisms and propagation phenomena are performed. Numerical examinations are presented to demonstrate the utilization of these solutions. Key Points: Floquet mode expansion of the scattering fields Decomposition of electromagnetic (EM) scattering mechanisms Asymptotic formulation of ray fields